Mechanisms of critical current limitation in YBCO thin film structures - Benacka, S.; Strbik, V.; Chromik, S.; Adam, R.; Darula, M.; Gazi, S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The limitation of critical current in high Tc superconducting YBCO thin films has a varied nature according to the quality of YBCO films. Our results showed that in strips from granular films the weak links of superconductor-normal metal-superconductor and superconductor-constriction-superconductor types were responsible for critical current limitation. In the YBCO strips with improved (preferential) crystallographic orientation a flux-creep critical current limitation was found and in the highly oriented YBCO strips the Ginzburg-Landau depairing mechanism approximated the critical current limitation for temperature close to Tc